Outdoor-indoor air pollution in urban environment: challenges and opportunity - Leung, Dennis Y. C. (Frontiers in Environmental Science, 2015)
With the continual improvement in our quality of life, indoor air quality has become an important area of concern in the 21st century. Indoor air quality is affected by many factors including the type and running conditions of indoor pollution sources, ventilation conditions, as well as indoor activities. Studies revealed that the outdoor environment is also an important factor that cannot be neglected for indoor air quality studies. In this review, the indoor and outdoor air pollution relationships obtained from different studies are discussed in order to identify the key factors affecting the indoor air quality. As climate change is recognized as imposing impacts on the environment, how it affects the indoor air quality and the health impacts to the occupants will be evaluated in this paper. The major challenges and opportunities in indoor/outdoor air pollution studies will be highlighted.